You are on page 1of 3

Solution Set 2

Handout October 16th 2013 Due October 23rd 2013

Solution 1
(i) Since the ball reaches a maximum height of 30 m, its velocity is 0 m s−1 there. So taking v = 0 m s−1 , s = 30 m, and a = −9.81 m s−2 (the acceleration due to gravity), we can calculate its initial velocity from v 2 = u2 + 2as. Rearranging u= = = v 2 − 2as (0 m s−1 )2 − 2(−9.81 m s−2 )(30 m) 588.6 (m s−1 )2

= 24.3 m s−1 . The ball is initially thrown at a speed 24.3 m s−1 . (ii) The ball is at the ground when its height s equals 0 metres. Using s = 2 ut + 1 2 at , this occurs when 1 1 0 = ut + at2 = t u + at . 2 2 The solutions are t = 0 s , when the ball is initially thrown, and t= 2u 2 × 24.3 m s−1 = = 4.95 s, −a 9.81 m s−2

when the ball reaches the ground again.
u (iii) The final velocity v of the ball is calculated by substituting t = − 2a into v = u + at, yielding

v =u+a −

2u a

= u − 2u = −u.

Hence the final velocity of the ball is −24.3 m s−1 . This can also be deduced by symmetry arguments.

Solution 2
(i) We obtain the following velocity-time graph of the boat’s motion: 1

velocity/m s−1 10

10 -5

20

40

50

time/s

(ii) The boat reaches its furthest distance in 40 seconds, after which time it has negative velocity and begins to move back towards the dock. Its total displacement during this time is given by the area under the velocity-time graph, 1 1 (10 s)(10 m s−1 ) + (10 s)(10 m s−1 ) + (20 s)(10 m s−1 ) = 250 m. 2 2 (iii) The overall displacement of the boat is the signed area under the v -t graph. From 40 to 50 seconds, the boat reverses back towards the dock, with 1 signed displacement 2 (10 s)(−5 m s−1 ) = −25 m. Using the result of part (ii), its final displacement from the dock is 250 m − 25 m = 225 m.

Solution 3
(i) Let t denote the time elapsed, starting from when the first stone is thrown. The initial speed u is 20 m s−1 , while the acceleration due to gravity a is −9.81 m s−2 . As a function of t, the height of the first stone is given by 1 s1 = ut + at2 . 2 As a function of t, the height of the second stone is given by 1 s2 = u(t − 1) + a(t − 1)2 2 for t ≥ 1 s. The time t at which the two stones collide is found by setting s1 = s2 , i.e., 1 1 ut + at2 = u(t − 1) + a(t − 1)2 . 2 2 After some algebra, this gives 1 1 u 0 = −u − at + a =⇒ t = − . 2 2 a Substituting in our values for u and a gives t= 1 20 m s−1 − = 2.54 s. 2 (−9.81 m s−2 ) 2

(ii) The height at which the two stones collide is found by evaluating either s1 or s2 at the time found in part (i). Let’s stick to symbols at first: u substituting t = 1 2 − a into s1 gives s1 = u 1 u − 2 a a u2 = − . 8 2a 1 + a 2 1 u − 2 a
2

Now substituting u = 20 m s−1 and a = −9.81 m s−2 yields s1 = − 9.81 m s−2 (20 m s−1 )2 = 19.16 m. + 8 2 × 9.81 m s−2

The situation is illustrated in the following displacement-time graph. Note that the two stones collide when the first is moving down, and the second is moving up.

height/m first stone second stone 20.39 19.16

1

2.54

4.08

5.08

time/s

3